2021
DOI: 10.3389/fonc.2021.736769
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor DNA as a Predictive Marker of Recurrence for Patients With Stage II-III Breast Cancer Treated With Neoadjuvant Therapy

Abstract: BackgroundPatients with stage II to III breast cancer have a high recurrence rate. The early detection of recurrent breast cancer remains a major unmet need. Circulating tumor DNA (ctDNA) has been proven to be a marker of disease progression in metastatic breast cancer. We aimed to evaluate the prognostic value of ctDNA in the setting of neoadjuvant therapy (NAT).MethodsPlasma was sampled at the initial diagnosis (defined as before NAT) and after breast surgery and neoadjuvant therapy(defined as after NAT). We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…The pre‐operative ctDNA detection rate of our K‐Track ® assay for all patients was 44.3%, similar to [ 34 ]; the rate in combined high‐risk groups was 59.6%, slightly lower than 63% [ 35 ] and 78% [ 6 ] detection rates in their respective high‐risk cohorts. These studies all used a much more extensive sequencing approach than K‐Track ® and the non‐inferiority of our result again supported both clinical and economic values of the assay.…”
Section: Discussionsupporting
confidence: 69%
“…The pre‐operative ctDNA detection rate of our K‐Track ® assay for all patients was 44.3%, similar to [ 34 ]; the rate in combined high‐risk groups was 59.6%, slightly lower than 63% [ 35 ] and 78% [ 6 ] detection rates in their respective high‐risk cohorts. These studies all used a much more extensive sequencing approach than K‐Track ® and the non‐inferiority of our result again supported both clinical and economic values of the assay.…”
Section: Discussionsupporting
confidence: 69%
“…In TNBC, numerous reports have indicated that ctDNA fraction is an important biomarker for chemotherapy response and tumor progression. It is well known that a high level of ctDNA after neoadjuvant chemotherapy (NAC) is associated with shorter progression-free survival and relapse-free survival [ 38 , 39 , 40 , 41 , 42 , 43 , 48 , 49 ]. Similarly, a concentration of circulating cell-free DNA above 264 ng/mL is a strong marker of increased risk of relapse [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al have achieved similar results on plasma samples from 95 breast cancer patients (among which 25 TNBC). In this report, the mutation and copy number state of a gene panel (TP53, PI3KCA, HER2, GATA3, CDH1, PTEN, AKT1, ESR1, S100A7-9, ZNF703, B2M, CCND1, c-MYC) were analyzed pre- and post-neoadjuvant chemotherapy (NAC) [ 48 ]. Li et al used a personalized QIAseq Targeted DNA Panel to amplify the coding region of chosen genes.…”
Section: Liquid Biopsy and Circulating Cell-free Nucleic Acids In Tnbcmentioning
confidence: 99%
See 2 more Smart Citations